Underwater Ambient Noise Measurement and Recording System - Baykut, Suleyman; Direk, Seyhmus; Gezer, Cengiz; Ulug, Ufuk; Akgul, Tayfun (IEEE, 2007)
In this study, a shallow water broadband acoustic receiver system is designed for collecting underwater acoustic data. The system is designed as a linear sensor array including 8 omni directional hydrophones. In order to collect the test data and conduct experiments a test system with one hydrophone is realized and a recording program interface is written prior to the implementation of the main system. Experiments are made in the aquarium, the test pool and the sea.